Arduino-based Mini Shaker for Automatic Chemical Solution Mixer - Hudha Wijaya, Nur; Friska Novela, Dian; Shahu, Nishith; Usman Sattar, Mian (Universitas Muhammadiyah Yogyakarta, 2020)
The purpose of the research was to make an Arduino-based mini shaker for automatic mixing of chemical solutions. The use of the tool was expected to save time and energy in the process of mixing chemical solutions, facilitate laboratory workers in mixing the chemical solutions quickly and efficiently, and for a safety reason in the laboratory. The design of this tool consists of a time sensor, speed sensor, microcontroller, motor driver and Dc motor. This tool can regulate the speed of a DC motor with three speeds namely 100 RPM low, 150 normal RPM, and 180 high RPM. Based on the results of motor speed measurements, the average error at the motor speed is low 1.4%, normal 2.5%, and high 2.54%, and the average error at the timer is 1 minute 0.03%, 2 minutes 0,1%, 3 minutes 0.05%, 4 minutes 0.016%, and 5 minutes 0.03%.